Inter‐observer agreement for the histological diagnosis of invasive lobular breast carcinoma. (10th December 2021) - Christgen, Matthias; Kandt, Leonie Donata; Antonopoulos, Wiebke; Bartels, Stephan; Van Bockstal, Mieke R; Bredt, Martin; Brito, Maria Jose; Christgen, Henriette; Colpaert, Cecile; Cserni, Bálint; Cserni, Gábor; Daemmrich, Maximilian E; et al.
Abstract: Invasive lobular breast carcinoma (ILC) is the second most common breast carcinoma (BC) subtype and is mainly driven by loss of E‐cadherin expression. Correct classification of BC as ILC is important for patient treatment. This study assessed the degree of agreement among pathologists for the diagnosis of ILC. Two sets of hormone receptor (HR)‐positive/HER2‐negative BCs were independently reviewed by participating pathologists. In set A (61 cases), participants were provided with hematoxylin/eosin (HE)‐stained sections. In set B (62 cases), participants were provided with HE‐stained sections and E‐cadherin immunohistochemistry (IHC). Tumor characteristics were balanced. Participants classified specimens as non‐lobular BC versus mixed BC versus ILC. Pairwise inter‐observer agreement and agreement with a pre‐defined reference diagnosis were determined with Cohen's kappa statistics. Subtype calls were correlated with molecular features, including CDH1 /E‐cadherin mutation status. Thirty‐five pathologists completed both sets, providing 4, 305 subtype calls. Pairwise inter‐observer agreement was moderate in set A (median κ = 0.58, interquartile range [IQR]: 0.48–0.66) and substantial in set B (median κ = 0.75, IQR: 0.56–0.86, p < 0.001). Agreement with the reference diagnosis was substantial in set A (median κ = 0.67, IQR: 0.57–0.75) and almost perfect in set B (median κ = 0.86, IQR: 0.73–0.93, p < 0.001). The median frequency of CDH1 /E‐cadherin mutations in specimens classified as ILC was 65% in set A (IQR: 56–72%) and 73% in set B (IQR: 65–75%, p < 0.001). Cases with variable subtype calls included E‐cadherin‐positive ILCs harboring CDH1 missense mutations, and E‐cadherin‐negative ILCs with tubular elements and focal P‐cadherin expression. ILCs with trabecular growth pattern were often misclassified as non‐lobular BC in set A but not in set B. In conclusion, subtyping of BC as ILC achieves almost perfect agreement with a pre‐defined reference standard, if assessment is supported by E‐cadherin IHC. CDH1 missense mutations associated with preserved E‐cadherin protein expression, E‐ to P‐cadherin switching in ILC with tubular elements, and trabecular ILC were identified as potential sources of discordant classification.